Planetary extravehicular activity (EVA) risk mitigation strategies for long-duration space missions - Blaze Belobrajdic (Nature Portfolio, 2021)
Abstract Extravehicular activity (EVA) is one of the most dangerous activities of human space exploration. To ensure astronaut safety and mission success, it is imperative to identify and mitigate the inherent risks and challenges associated with EVAs. As we continue to explore beyond low earth orbit and embark on missions back to the Moon and onward to Mars, it becomes critical to reassess EVA risks in the context of a planetary surface, rather than in microgravity. This review addresses the primary risks associated with EVAs and identifies strategies that could be implemented to mitigate those risks during planetary surface exploration. Recent findings within the context of spacesuit design, Concept of Operations (CONOPS), and lessons learned from analog research sites are summarized, and how their application could pave the way for future long-duration space missions is discussed. In this context, we divided EVA risk mitigation strategies into two main categories: (1) spacesuit design and (2) CONOPS. Spacesuit design considerations include hypercapnia prevention, thermal regulation and humidity control, nutrition, hydration, waste management, health and fitness, decompression sickness, radiation shielding, and dust mitigation. Operational strategies discussed include astronaut fatigue and psychological stressors, communication delays, and the use of augmented reality/virtual reality technologies. Although there have been significant advances in EVA performance, further research and development are still warranted to enable safer and more efficient surface exploration activities in the upcoming future.